An Analysis of governance, official development assistance and economic growth in developing and transition countries - Niaz Ali, KHAN (KDI School, 2017)
This paper investigates the Impact of Good governance on effective utilization of Official Development Assistance (ODA) in transition countries as compared to developing countries. We use a data covering a panel of 32transition countries in the, from 1996 to 2013. The empirically study finds strong evidence supporting a positive impact of good governance on ODA. We find strong and robust evidence that governance has a positive impact on effectively of ODA. Therefore, the study reached on conclusion that effective aid utilization required institutions efficiency. This suggests that the other in order to reap the best benefits of ODA improvement in Governance is the first and foremost milestone to be achieved in transition countries as in the case of other developing countries. Both developing and transition economy need institutions reform unless any reform effective aid utilization is dream for both developing and transition countries.
Thesis(Master) --KDI School:Master of Public Policy,2017